Photo-Induced Antitumor Effect of 3,6-Bis(1-methyl-4-vinylpyridinium) Carbazole Diiodide - Chou, Ya-Shuan (Hindawi Publishing Corporation, 2013)
We have applied a fluorescent molecule 3,6-bis(1-methyl-4-vinylpyridinium) carbazole diiodide (BMVC) for tumor targeting and treatment. In this study, we investigated the photo-induced antitumor effect of BMVC. In vitro cell line studies showed that BMVC significantly killed TC-1 tumor cells at light dose greater than 40 J/cm(2). The fluorescence of BMVC in the tumor peaked at 3 hours and then gradually decreased to reach the control level after 24 hours. In vivo tumor treatment studies showed BMVC plus light irradiation (iPDT) significantly inhibited the tumor growth. At day 24 after tumor implantation, tumor volume was measured to be 225 ± 79 mm(3), 2542 ± 181 mm(3), 1533 ± 766 mm(3), and 1317 ± 108 mm(3) in the iPDT, control, light-only, and BMVC-only groups, respectively. Immunohistochemistry studies showed the microvascular density was significantly lower in the iPDT group. Taken together, our results demonstrated that BMVC may be a potent tumor-specific photosensitizer (PS) for PDT.